2021
DOI: 10.3390/app11020872
|View full text |Cite
|
Sign up to set email alerts
|

Retrospective Analysis of the Effect of Three-Dimensional Preformed Titanium Mesh on Peri-Implant Non-Contained Horizontal Defects in 100 Consecutive Cases

Abstract: This study aimed to clinically and radiographically evaluate the results of guided bone regeneration (GBR) using three-dimensional preformed titanium mesh (3-D-PFTM) for non-contained horizontal defects in 100 consecutive cases. This study involved 100 patients (129 implants) with peri-implant non-contained horizontal defects. The patients were divided into three groups: 3-D-PFTM alone (Group 1), 3-D-PFTM plus cross-linked collagen membrane (Group 2), and 3-D-PFTM plus non-cross-linked collagen membrane (Group… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
15
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(15 citation statements)
references
References 35 publications
0
15
0
Order By: Relevance
“…A study by Lim et al [ 29 ] reported that the exposure rate was not significantly reduced even with the additional use of a resorbable collagen membrane, but Strietzel et al [ 30 ] reported that when a collagen membrane was used during GBR, the fibrous tissue grew within the collagen membrane and functioned as a barrier for space maintenance to prevent flap dehiscence. In our previous study, where only 3D-PFTM was used, an exposure rate of 11.8% was observed, whereas when CCM and NCCM were additionally used together, the exposure rate was reduced to 4.2% and 5.0%, respectively [ 15 ]. In this study, when CCM and NCCM were additionally used together with 3D-PFTM, the exposure rate was 6.67%, showing a slightly increased exposure rate compared to that reported in a previous study.…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…A study by Lim et al [ 29 ] reported that the exposure rate was not significantly reduced even with the additional use of a resorbable collagen membrane, but Strietzel et al [ 30 ] reported that when a collagen membrane was used during GBR, the fibrous tissue grew within the collagen membrane and functioned as a barrier for space maintenance to prevent flap dehiscence. In our previous study, where only 3D-PFTM was used, an exposure rate of 11.8% was observed, whereas when CCM and NCCM were additionally used together, the exposure rate was reduced to 4.2% and 5.0%, respectively [ 15 ]. In this study, when CCM and NCCM were additionally used together with 3D-PFTM, the exposure rate was 6.67%, showing a slightly increased exposure rate compared to that reported in a previous study.…”
Section: Discussionmentioning
confidence: 99%
“…Regardless of the presence or absence of cross-linking, a horizontally stable HG of 2 mm or more was observed even after 6 months of GBR. In our previous study including the posterior region, the HGR was 71.0% for 3D-PFTM only, whereas it was 84.2% in the CCM group and 84.0% in the NCCM group, when the resorbable membrane was used together [ 15 ]. In an animal experiment by Shin et al [ 36 ], increased HGR was observed in the Ti mesh group using the resorbable collagen membrane compared to that in the group treated with Ti mesh alone.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations